Biomechanical analysis of wood processing work in tropical forest regions: A study in Midwest Brazil - Soranso, Denise R.; Minette, Luciano J.; Lima, Roldão Carlos A. [UNESP]; Schettino, Stanley; Nascimento, Glícia Silvania P.; Bermudes, Wanderson L.; Costa Campos, Julio Cesar (Taylor & Francis, 2023)
In the wood processing industry, working with machines exposes workers to occupational risks. This study evaluates the biomechanics of work activities carried out in a wood processing operation in tropical forest regions to identify risks associated with the development of musculoskeletal injuries. Data were collected in a wood processing industry from a tropical forest region in Midwest Brazil. Forty forest workers were evaluated, equivalent to 100% of the population of the company participating in the study. Biomechanical movements were measured using the Three-Dimensional Biomechanical Model for Predicting Stances and Static Forces. There was a risk of injury to the joints of the upper limbs (wrists and shoulders), as well as to the torso. When splitting and manually stacking wood, a risk of spinal injury was identified. All workers had a high risk of developing injuries in all joints evaluated in addition to a risk of serious spinal injury. In this way, the development of these activities without any ergonomic interventions makes the risk of developing musculoskeletal injuries in the workers involved imminent, with consequent early professional incapacity.
Keywords: Musculoskeletal injuries; sawmill; spine; work conditions; worker’s health